Comparação entre os sistemas construtivos de alvenaria estrutural e paredes de concreto monolíticas moldadas in loco - Lara, Bruna Stocco de (2016)
New technologies in building systems are becoming more popular in the national market. In 2009, in order to meet the housing deficit generated by the unplanned development in Brazil, the federal government created the program Minha Casa Minha Vida, which resulted in a serie of changes in the way of how popular buildings in the country way are made. After setting up the program arose the need to have greater control over the new works, thus giving upgrade to PBQP-H (Brazilian Program of Habitat Quality and Productivity) which in turn led builders to seek unconventional building systems. This study deals with just two of these systems, structural masonry and walls of monolithic concrete molded on site, comparing them as the cost and time. The need for this analysis is based on the difficulties currently faced by national construction companies to obtain interesting financial results in a little hot market and with small profit margins, thus a constructive system presenting waste and term lower performance, is of extreme interest. In order to assist in the most advantageous construction system selection will be presented comparative data, including a budget of a model block for each system and their schedules as well as further analysis of variance overhead, reaching a parameter spreadsheet that allows to choose the better construction system for a given number of blocks of apartments. The compilation of these data arrives at a parameterization sheet, which allows choosing the best construction system for a given number of blocks of apartments. These allow to conclude that the construction system of structural masonry is more advantageous to perform up to 3 blocks of apartments and amounts above, within the simulation would be more interesting to select the structural system of concrete monolithic walls molded on site.